Advances in the study of apathy related to cerebral small vessel disease - Bu, Shuo-han; Hu, Xin-zhu; Su, Zhe; Li, Li-tao (Frontiers in Neurology, 2025)
Cerebral small vessel disease (CSVD) is a complex clinical-imaging pathological syndrome caused by small vessel lesions in the brain, which is characterized by aging-related, insidious onset and slow progression. Apathy is a key component of the common neuropsychiatric symptoms among CSVD patients, severely affecting their daily lives and social functioning. Moreover, there are fewer studies on CSVD-related apathy, and greater attention should be paid to this condition in clinical practice. This article describes the latest research advances in the concept, epidemiological features, pathogenesis, assessment and diagnosis, imaging and biomarkers, and treatment of CSVD-related apathy, aiming to serve as a reference for the clinical diagnosis and prevention of CSVD-related apathy.